INHIBITORY EFFECT OF ESSENTIAL OILS ON EXTRACELLULAR LIPASE ACTIVITY OF MALASSEZIA GLOBOSA - SHUBHANGI MUGAL,; RANJANA VERMA,; RENU MISHRA,; SHIKHA MANDLOI., (International Journal of Pharma and Bio Sciences, 2013)
Pityriasis capitis is a common scalp disorder caused by a fungus Malassezia globosa. The mechanism of Pityriasis capitis includes Malassezia-induced fatty acid metabolism, particularly lipase-mediated breakdown of sebaceous lipids and release of irritating free fatty acids. We report that extracellular lipase activity was detected in Malassezia globosa. The presence of lipase enzyme was performed in specific media on Petri dishes for formation of a zone.In this article, the effect of Cymbopogon citratus and Zingiber officinale essential oils on the extracellular lipase activity of Malassezia globosa had been studied by titrametric method. At the end of titration 4 µmol fatty acid/ml of reaction mixture was released in the presence of Cymbopogon citratus oil and 7µmol of fatty acid/ml of reaction mixture was liberated in the presence of Zingiber officinale oil. It was found that both essential oils strongly inhibit the lipase activity of M. globosa at a lower concentration.